Clostridioides difficile Senses and Hijacks Host Heme for Incorporation into an Oxidative Stress Defense System - Knippel, Reece J. (Cell Host Microbe, 2020)
Clostridioides difficile infection of the colon leads to severe inflammation and damage to the gastrointestinal epithelium due to the production of potent toxins. This inflammatory tissue damage causes the liberation of high concentrations of host heme at infection sites. Here, we identify the C. difficile heme sensing membrane protein system (HsmRA) and show this operon induces a protective response that repurposes heme to counteract antimicrobial oxidative stress responses. HsmR senses vertebrate heme, leading to increased expression of the hsmRA operon and subsequent deployment of HsmA to capture heme and reduce redox damage caused by inflammatory mediators of protection and antibiotic therapy. Strains with inactivated hsmR or hsmA have increased sensitivity to redox active compounds and reduced colonization persistence in a murine model of relapse C. difficile infection. These results define a mechanism exploited by C. difficile to repurpose toxic heme within the inflamed gut as a shield against antimicrobial compounds.